1999
DOI: 10.1016/s0735-1097(99)00074-1
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker lead extraction with the laser sheath: results of the pacing lead extraction with the excimer sheath (PLEXES) trial11No financial support was received for performing the procedures or collecting the data, or for data analysis.

Abstract: Laser-assisted pacemaker lead extraction has significant clinical advantages over extraction without laser tools and is associated with significant risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(60 citation statements)
references
References 10 publications
0
58
0
2
Order By: Relevance
“…Byrd [11] reported the first excimer laser-assisted pacemaker lead extraction in 1996. The multicenter randomized pacing lead extraction with the excimer sheath (PLEXES) trial found that laser-assisted extraction was more efficacious than non-laser techniques in 301 patients with no statistically significant difference in life-threatening complications between the laser and the non-laser groups [12]. However, a subsequent nonrandomized European multicenter study of excimer laser-assisted pacemaker and ICD lead extractions in 292 patients reported a 5.1% complication rate [13].…”
Section: Discussionmentioning
confidence: 99%
“…Byrd [11] reported the first excimer laser-assisted pacemaker lead extraction in 1996. The multicenter randomized pacing lead extraction with the excimer sheath (PLEXES) trial found that laser-assisted extraction was more efficacious than non-laser techniques in 301 patients with no statistically significant difference in life-threatening complications between the laser and the non-laser groups [12]. However, a subsequent nonrandomized European multicenter study of excimer laser-assisted pacemaker and ICD lead extractions in 292 patients reported a 5.1% complication rate [13].…”
Section: Discussionmentioning
confidence: 99%
“…Serious complications of forceful lead extraction, including myocardial rupture, are possible [52][53][54][55][56][57], and thoracotomy with cardiopulmonary bypass may be required for removal if nonsurgical techniques fail [58]. Excimer laser sheaths appear to be more effective than direct traction or telescoping sheaths [83,84]. In a randomized trial of 301 patients with implanted pacemaker leads, failed nonlaser extraction was completed with laser tools 88% of the time [84].…”
Section: Management Of Cardiac Device Infectionsmentioning
confidence: 99%
“…Excimer laser sheaths appear to be more effective than direct traction or telescoping sheaths [83,84]. In a randomized trial of 301 patients with implanted pacemaker leads, failed nonlaser extraction was completed with laser tools 88% of the time [84]. In the case series from Mayo Clinic, 11% of patients had complications of percutaneous lead extraction, including damage to cardiac valves, venous lacerations, hemorrhage and lead tip fracture requiring surgical intervention [38].…”
Section: Management Of Cardiac Device Infectionsmentioning
confidence: 99%
“…The femoral approach using mechanical dilation has been reported 3. However, laser extraction has the advantage over mechanical dilator extraction in that the former has higher rates of complete removal than the latter 4. Although no reports regarding the efficacy of laser extraction via femoral access have been published, we presume higher rates of complete extraction.…”
Section: Discussionmentioning
confidence: 80%